Guardian of Faith: Comparative Insights of Teaching Islamic Theology in Indonesian and Malaysian Pesantren - Zainul Abas; Anas Tajudin; Arif Nugroho; Heldy Ramadhan Putra (Universitas Pesantren Kh abdul Chalim Mojokerto, 2025)
A notable lacuna in the literature exists regarding research on Islamic theological education in Southeast Asian pesantren. This current state underscores the imperative for comprehensive investigation, particularly through the application of comparative analyses of pedagogical approaches. The present study comparatively analyzes how pedagogical approaches, institutional factors, and theological orientations shape Islamic theology instruction in Indonesian and Malaysian pesantren. A comparative case study was conducted in one pesantren from each country, utilizing semi-structured interviews with eight participants (heads, teachers, senior students) and document analysis, with data analyzed thematically. Findings indicate Indonesian pesantren prioritize traditional, memorization-based methods and theological conservatism due to institutional autonomy. At the same time, Malaysian counterparts adopt structured, curriculum-based approaches influenced by state involvement and national standards. The study highlights how both contexts negotiate orthodoxy and modernity differently, offering implications for developing culturally grounded and pedagogically responsive Islamic theological curricula and teacher training.